Characterization of dermatological diagnoses among hospitalized patients experiencing homelessness. (1st January 2022) - Zakaria, A.; Amerson, E. H.; Kim‐Lim, P.; Fox, L.; Chang, A. Y.
Summary: While previous studies have characterized the types of dermatological disease among people experiencing homelessness (PEH) in the outpatient setting, dermatological disease among hospitalized PEH has never been evaluated. Therefore, we performed a cross‐sectional analysis of hospitalized patients who received dermatology consultations at two San Francisco hospitals between March 2018 and March 2020 and compared the odds of diagnostic categories between PEH and patients with stable housing. In both unadjusted and adjusted analyses, PEH had significantly higher odds of bacterial skin infections [adjusted odds ratio (aOR) = 2.29, 95% CI 1.46–3.61], ectoparasitic disease (aOR = 9.43, 95% CI 3.79–23.47), psoriasis or seborrhoeic dermatitis (aOR = 2.50, 95% CI 1.43–4.36) and venous stasis or lymphoedema (aOR = 2.54, 95% CI 1.23–5.27) and significantly lower odds of drug reactions (aOR = 0.34, 95% CI 0.18–0.67). Overall, these findings highlight the unique dermatological challenges among hospitalized PEH and suggest potential strategies to facilitate equitable dermatology care delivery.